2014
DOI: 10.1165/rcmb.2013-0385oc
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Vascular Endothelial Growth Factor Secreted by Mesenchymal Stem Cells in Hyperoxic Lung Injury

Abstract: Intratracheal transplantation of human umbilical cord blood (UCB)-derived mesenchymal stem cells (MSCs) protects against neonatal hyperoxic lung injury by a paracrine rather than a regenerative mechanism. However, the role of paracrine factors produced by the MSCs, such as vascular endothelial growth factor (VEGF), has not been delineated. This study examined whether VEGF secreted by MSCs plays a pivotal role in protecting against neonatal hyperoxic lung injury. VEGF was knocked down in human UCB-derived MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 42 publications
3
89
0
Order By: Relevance
“…Lung inflammatory cytokines and VEGF levels showed significant positive and negative correlations with brain weight, respectively, at P14. We have shown that the protective effects of MSC transplantation may primarily be mediated by a paracrine rather than a regenerative mechanism, and have highlighted the critical role of growth factors, including VEGF, in mediating the antioxidative, anti-inflammatory, and antiapoptotic paracrine effects of MSC transplantation (20). Taken together, these findings suggest that the neuroprotective …”
mentioning
confidence: 76%
“…Lung inflammatory cytokines and VEGF levels showed significant positive and negative correlations with brain weight, respectively, at P14. We have shown that the protective effects of MSC transplantation may primarily be mediated by a paracrine rather than a regenerative mechanism, and have highlighted the critical role of growth factors, including VEGF, in mediating the antioxidative, anti-inflammatory, and antiapoptotic paracrine effects of MSC transplantation (20). Taken together, these findings suggest that the neuroprotective …”
mentioning
confidence: 76%
“…In addition, TLR-4 in MSCs plays pivotal roles in eliminating pathogens by augmenting antibacterial effects and reducing host tissue injuries by attenuating the inflammatory response (90,91). Collectively, these studies suggest that key paracrine factors secreted by MSCs from the same source play important roles in mediating the therapeutic effects of MSCs in different preclinical disease models (11,13,48), suggesting that there is a crosstalk and interplay between the host tissue and transplanted MSCs (61,92). Therefore, unlike drug treatments that deliver a single agent at a specific dose, transplanted MSCs act as a "paracrine factors factory" that sense the microenvironment of the injury site and secrete various paracrine factors that exert several reparative functions, including antiapoptotic, anti-inflammatory, antioxidative, antifibrotic, and/or antibacterial effects in response to local microenvironmental cues to enhance the regeneration of damaged tissue (86).…”
Section: Environmental Cues Trigger the Secretion Of Paracrine Factorsmentioning
confidence: 93%
“…Therefore, a multifaceted therapeutic agent might be necessary to improve outcomes of patients with these intractable neonatal disorders. The pleiotropic beneficial effects of stem cell therapy, such as antiapoptotic, anti-inflammatory, antifibrotic, and antioxidative effects, have been observed in various animal models of BPD (5)(6)(7)(8)10), severe IVH (13-15), or HIE (11,25,26). Furthermore, in addition to their beneficial antiinflammatory effects, antibacterial activity of transplanted stem cells were observed in an animal model of Escherichia coli pneumonia (27).…”
Section: Pleiotropic Protective Effects Of Stem Cell Therapiesmentioning
confidence: 99%
“…Various preclinical data support the therapeutic potential of transplantation with mesenchymal stem cells (MSCs) for treating various intractable neonatal disorders including bronchopulmonary dysplasia (BPD) 11, 12, 13, 14 and hypoxic ischemic encephalopathy (HIE) 15. Human umbilical cord blood (UCB) is a promising source of MSCs.…”
Section: Introductionmentioning
confidence: 99%